2020
DOI: 10.1007/s11420-020-09759-3
|View full text |Cite
|
Sign up to set email alerts
|

Reporting Clinical Significance in Hip Arthroscopy: Where Are We Now?

Abstract: Background Although p values are standard for reporting statistical significance of patient-reported outcome measures (PROMs), the shift toward clinically important outcome values, including minimal clinically important difference (MCID) and substantial clinical benefit (SCB), necessitates re-evaluation of the current literature. Questions/Purposes We sought to answer two questions regarding studies on primary hip arthroscopy performed for the treatment of femoroacetabular impingement syndrome (FAIS). (1) Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
(49 reference statements)
1
4
0
Order By: Relevance
“…A secondary objective of this review was to evaluate outcome reporting and attempt to delineate the most relevant clinical outcome PROMs. Although eight unique PROMs were identified, 83% of studies included the mHHS, which is consistent with the prior literature, suggesting that it is the most commonly used PROM following hip arthroscopy [ 19 , 49 , 50 ]. This suggests that PROM usage in hip arthroscopy is fairly homogenous, compared, for example, to PROM use in the shoulder where there are 19 commonly used PROMs, with no one used in more than 27% of studies [ 51 ].…”
Section: Discussionsupporting
confidence: 74%
“…A secondary objective of this review was to evaluate outcome reporting and attempt to delineate the most relevant clinical outcome PROMs. Although eight unique PROMs were identified, 83% of studies included the mHHS, which is consistent with the prior literature, suggesting that it is the most commonly used PROM following hip arthroscopy [ 19 , 49 , 50 ]. This suggests that PROM usage in hip arthroscopy is fairly homogenous, compared, for example, to PROM use in the shoulder where there are 19 commonly used PROMs, with no one used in more than 27% of studies [ 51 ].…”
Section: Discussionsupporting
confidence: 74%
“…In recent years, efforts to define improvements in outcomes for patients have been increasing. 41 These outcomes include the MCID and PASS and should surely be the benchmark for treatment evaluation. However, it is important to acknowledge the results for the HAGOS and iHOT-12 score.…”
Section: Discussionmentioning
confidence: 99%
“…23,25 Similar systematic reviews have also reported that >90% of hip arthroscopy outcome studies achieved the MCID and SCB on the HOS but have noted that only 25% achieved the PASS. 18,30 Of the hip arthroscopy outcome studies in servicemembers, only 2 have utilized validated nonarthritic outcome scores, but they have not analyzed these outcomes in terms of clinically meaningful benefits. A randomized controlled trial of US servicemembers treated with either arthroscopic surgery or physical therapy for FAI demonstrated significant improvements among surgically treated patients at 2 years on the 33-item International Hip Outcome Tool and HOS-ADL but not on the HOS-S. 19 A prospective study of British servicemembers treated with hip arthroscopy for FAI reported a significantly improved NAHS at 1 year.…”
Section: Discussionmentioning
confidence: 99%